Edukasi Remaja Mengenai Pernikahan Usia Dini dan Implementasi Policy Brief: Pencegahan Pernikahan Usia Dini - Nina Damayanti; Surtiyoni, Endang; Monanisa (CARADDE: Jurnal Pengabdian Kepada Masyarakat, 2024)
The purpose of this PKM is to educate teenagers and parents about early marriage and to implement a policy brief for Karang Taruna members in Mekar Jaya Village to create a sustainable Karang Taruna work program and make teenagers have positive activities and activities. This PKM program involves teenagers, parents, and members of Karang Taruna Mekar Jaya Village. The method provided is in the form of education that is carried out in depth to strengthen the knowledge of teenagers and parents about early marriage, in addition, training is also provided on the implementation of policy briefs to create and improve Karang Taruna work programs. Data collection was carried out pre-post test, discussion. The results obtained showed an increase in adolescent knowledge about the age limit for early marriage, which initially said the age of 13-15 years by 63%, increasing to the age of 19-20 years by 93%. Likewise, with the knowledge of parents, initially 71% said that the age included in early marriage was 16-18 years, then increased to the age of 19-20 years by 89%. In conclusion, this PKM activity was stated to be able to increase the knowledge of the community in Mekar Jaya Village about early marriage, and it is hoped that the number of early marriages can decrease every year.